2013
DOI: 10.1016/j.taap.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Human metabolites of synthetic cannabinoids JWH-018 and JWH-073 bind with high affinity and act as potent agonists at cannabinoid type-2 receptors

Abstract: K2 or Spice is an emerging drug of abuse that contains synthetic cannabinoids, including JWH-018 and JWH-073. Recent reports indicate that monohydroxylated metabolites of JWH-018 and JWH-073 retain high affinity and activity at cannabinoid type-1 receptors (CB1Rs), potentially contributing to the enhanced toxicity of K2 compared to marijuana. Since the parent compounds also bind to cannabinoid type-2 receptors (CB2Rs), this study investigated the affinity and intrinsic activity of JWH-018, JWH-073 and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 41 publications
5
64
0
2
Order By: Relevance
“…Metabolite profiling data obtained from our human hepatocyte study proposes metabolites useful for identifying RCS-4 intake. Identification of RCS-4 metabolites is critical because in vitro and in vivo studies showed that Phase I and II metabolites of JWH-018 and JWH-073 retain strong binding affinity and exhibit agonist potency at CB 1 and CB 2 receptors [2830]. These metabolites should be synthesized for use as reference standards in clinical and forensic laboratory RCS-4 urine screening and confirmation testing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolite profiling data obtained from our human hepatocyte study proposes metabolites useful for identifying RCS-4 intake. Identification of RCS-4 metabolites is critical because in vitro and in vivo studies showed that Phase I and II metabolites of JWH-018 and JWH-073 retain strong binding affinity and exhibit agonist potency at CB 1 and CB 2 receptors [2830]. These metabolites should be synthesized for use as reference standards in clinical and forensic laboratory RCS-4 urine screening and confirmation testing.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, metabolites of JWH-018 and JWH-073 were also shown to have strong binding affinity and potency at human CB 1 and CB 2 receptors [2830]. Synthetic cannabinoids are extensively metabolized in humans [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…JWH-018, JWH-073 and CP 47,497-C8-homolog bind to cannabinoid CB1 receptors, inhibit neurotransmission in hippocampal neurons and facilitate cannabinoid CB1 receptor internalization (Atwood et al, 2010, 2011; Brents et al, 2012; Showalter et al, 1996). In addition, JWH-018 and JWH-073 bind to human cannabinoid CB2 receptors and act as agonists (Rajasekaran et al, 2013). Since these compounds share their mechanism of action with Δ 9 -THC, a major active component of marijuana, it is not surprising that JWH-018 and JWH-073 fully substituted for the discriminative stimulus effects of Δ 9 -THC in rhesus monkeys (Ginsburg et al, 2012) and that monkeys developed cross-tolerance to JWH-018 and JWH-073 following repeated administration of Δ 9 -THC (Hruba et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2016;7(10):455-458 thought to play a role in control of pain and emesis. SCs are full agonists of CB receptors with biologically active metabolites [9][10][11]. SCs are in vogue, especially among the young generation who use it for relaxation and recreation without being detected on routine toxicology screens [10,12].…”
Section: Discussionmentioning
confidence: 99%